2020
DOI: 10.36941/jesr-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

MGMP Teacher Organization Empowerment in Improving Students' Problem Solving Ability

Abstract: This study aims to determine the effect of MGMP teacher organization empowerment on the quality of teacher learning, and its impact on improving students' ability to solve problems. The writing is part of a study on the empowerment of MGMP conducted in five cities in Indonesia in mid-2019. The sample of this study was teachers with each MGMP taken 25 of those classified as seniors (more than 10 years) as teachers (125 people in total). Data collection was carried out through questionnaires, focus group discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The various potential abilities of teachers in teaching social studies subjects, the different qualities of teachers, and the increasing demands of teacher professionalism in facing technological progress are consequences of the changes (Sahudra et al, 2021). Hence, Social Studies teachers gather in a professional learning community to seek input, facilitate communication, consultation, exchange of experiences, and recommendations to find solutions to overcoming emerging problems (Daryanto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The various potential abilities of teachers in teaching social studies subjects, the different qualities of teachers, and the increasing demands of teacher professionalism in facing technological progress are consequences of the changes (Sahudra et al, 2021). Hence, Social Studies teachers gather in a professional learning community to seek input, facilitate communication, consultation, exchange of experiences, and recommendations to find solutions to overcoming emerging problems (Daryanto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its strengths, there was also a weakness in the practice of MGMP. Daryanto et al (2020) found that scheduling and teacher assigning could hinder MGMP from strengthening teacher competencies.…”
Section: Introductionmentioning
confidence: 99%